2019
DOI: 10.1016/j.endinu.2019.02.003
|View full text |Cite
|
Sign up to set email alerts
|

Adipokines, cortisol and cytokine alterations in recent onset anorexia nervosa. A case–control study

Abstract: Introduction: Psychological and neuroendocrine alterations are typical characteristics in anorexia nervosa patients. The role of adipokines and cytokines as mediators of body systems' adaptations to the patients' abnormal eating behavior is not well understood. The duration of disease seems to be a determinant of nutritional status and associated hormone changes. We aimed to assess whether alterations in adipokines, cytokines and cortisol do already exist in patients with a recent disease onset by means of a c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 28 publications
(33 reference statements)
0
7
0
Order By: Relevance
“…By contrast, other studies did not find any significant relationship between SES and AN [7,25,26]. In a Spanish cohort of patients with AN, 53.7% were in status V (highest SES), and 22% in status IV; the prevalence was not different from healthy adolescents, and no ethnic minority status was reported [27].…”
Section: Discussionmentioning
confidence: 66%
“…By contrast, other studies did not find any significant relationship between SES and AN [7,25,26]. In a Spanish cohort of patients with AN, 53.7% were in status V (highest SES), and 22% in status IV; the prevalence was not different from healthy adolescents, and no ethnic minority status was reported [27].…”
Section: Discussionmentioning
confidence: 66%
“…IL-1β and IL-6 were significantly increased in previous metanalyses ( 9 , 10 ) and some recent publications ( 19 , 47 , 55 ); however, several current studies could not reproduce these findings or only reproduced them partially ( 10 , 25 , 47 , 56 ). Again, findings in adolescents were mixed ( 20 , 36 , 37 ). Interestingly, while the study with the relatively older adolescent sample found an increase in IL-1β and IL-6 ( 20 ), in the two younger samples of the three with the shorter duration of illness, only IL-1β was increased ( 36 ) or IL-1β did not differ and IL-6 even showed a tendency to be decreased ( p = 0.152) ( 37 ).…”
Section: Discussionmentioning
confidence: 95%
“…This effect had been found in two large metanalyses ( 9 , 10 ) and several studies since ( 19 , 20 , 23 , 47 ). However, there is also a very well-controlled recent report challenging this finding ( 27 ), and adolescent findings are mixed ( 20 , 36 , 37 ). Elevated TNF-α serum levels decreased during short-term weight recovery in our sample and were no longer significantly altered at discharge.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations